Pattern of Psychiatric illness among Tuberculosis Patients (Anwer Khan Modern Medical College Journal, 2017)
Background: The incidence of tuberculosis is very high in Bangladesh. There is a high prevalence of psychiatric illness among tuberculosis patients. But primary care physicians and specialists do not screen this association. The aims of this study were to evaluate the incidence and pattern of psychiatric illness in tuberculosis patients.Methodology: The study population included those patients who were coming for treatment in DOTs corner of Rajshahi Medical College Hospital between July 2014 - February 2015 (Eight months). Each patient underwent a detailed psychiatric evaluation by a consultant psychiatrist once they were medically stable. Details included socio-demographic data, psychiatric diagnosis and treatment outcome. All data was tabulated and analyzed using SPSS-16.Result: Among the total 350 tuberculosis patients, total 108 patients (31%) were diagnosed with psychiatric problems. Most of them are male (71%), less than 40 years of age (70%) with no previous psychiatric illness (98%). Depression (n=43, 40%) and Anxiety (n=33, 31%) were the commonest psychiatric illness diagnosed. Fear of disease outcome was the commonest precipitating factor found (66%). After the psychiatric treatment, 94% improved clinically.Conclusion: Detecting the level of psychiatric illness among tuberculosis patients at early stage will improve continuation and adherence to treatment. A referral system` to psychiatrists by physicians needs to develop to screen the mental disorder symptoms to treat these co morbidities.Anwer Khan Modern Medical College Journal Vol. 6, No. 2: July 2015, P 25-29